Analysis of Financial Aspects of Feasibility and Strategy for the Development of Reyog Craftsmen after the Construction of the Industrial Center in Ponorogo Regency - Najib Zamroni; Rochmat Aldy Purnomo; Sayid Abas; Slamet Santoso; Yeni Cahyono (Trunojoyo University of Madura, 2021)
Reyog handicraft industry is one of the leading SMEs in Ponorogo Regency. In early 2020, the Government of Ponorogo Regency established a new building as a production and promotion center for SMEs actors, namely the Industrial Center. This research aims to analyze the feasibility of business financial aspects and development strategies of reyog craftsmen after the construction of industrial centers. Research method using quantitative descriptive approach, informant selected using purposive sampling technique as many as 9 craftsmen. The method of data retrieval through interviews combined with a list of open questionnaires and field observations. Feasibility analysis uses NPV, PBP, IRR and B/C Ratio calculations, while development strategies are analyzed with SWOT. The results of the financial feasibility analysis of 3 types of handicrafts, namely barongan head, bujangganong mask and kelonosewandono mask indicate that the development of reyog handicraft business is feasible and continued. Swot analysis results related to the development strategy used by craftsmen consists of market penetration, product development and market development, including expanding market share by utilizing social media, maintaining the quality of raw materials used production, prioritizing the production of goods that have a faster turnover, have a stock of raw materials production for several months and maintain the prevailing price standards in the market.